Elementary School Students' Learning Motivation with the Presence of Online Games - Amelia Salsabila Putri; Irawan Suprapto (LPPM Undiksha, 2026)
The use of online games among elementary school students is increasing, raising concerns about their learning motivation and academic performance. Excessive gaming makes students more focused on the virtual world, disrupting concentration and interest in learning. This study aims to analyze the negative impact of online games on elementary students' learning motivation. The research employed a Systematic Literature Review (SLR) design, examining 10 accredited scientific articles from Google Scholar and SINTA published between 2020 and 2024. The study subjects were elementary school students, with inclusion criteria focusing on online games and learning motivation. The research methods included identification, selection, and descriptive analysis of the articles. The results indicate that online games reduce learning motivation, decrease focus during lessons, cause task neglect, and contribute to lower academic achievement and behavioral issues. The study’s implications emphasize the need for parental and teacher supervision, as well as early digital literacy education. In conclusion, proper management of online game usage is essential to maintain students’ motivation and academic performance.